Inflation expectations, inflation target credibility and the COVID-19 pandemic: New evidence from Germany - Winnie Coleman; Dieter Nautz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2021)
Using the exact wording of the ECB's definition of price-stability, we started a representative online survey of German citizens in January 2019 that is designed to measure long-term inflation expectations and the credibility of the inflation target. Our results indicate that credibility has decreased in our sample period, particularly in the course of the deep recession implied by the COVID-19 pandemic. Interestingly, even though inflation rates in Germany have been clearly below 2% for several years, credibility has declined mainly because Germans increasingly expect that inflation will be much higher than 2% over the medium term. We investigate how inflation expectations and the impact of the pandemic depend on personal characteristics including age, gender, education, income, and political attitude.
Keywords: E31; E52; E58; 330; Credibility of Inflation Targets; Household Inflation Expectations; Expectation Formation; Online Surveys; Covid-19 Pandemic